2009
DOI: 10.1073/pnas.0902146106
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive response by state-dependent inactivation

Abstract: Many membrane channels and receptors exhibit adaptive, or desensitized, response to a strong sustained input stimulus. A key mechanism that underlies this response is the slow, activitydependent removal of responding molecules to a pool which is unavailable to respond immediately to the input. This mechanism is implemented in different ways in various biological systems and has traditionally been studied separately for each. Here we highlight the common aspects of this principle, shared by many biological syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 34 publications
1
57
0
Order By: Relevance
“…The adaptive properties of kinetic models that represent biochemical processes including neurotransmitter receptors have recently been analyzed from a theoretical point of view (Friedlander and Brenner, 2009). This previous work showed that first order kinetic systems similar to the type discussed here can change their gain when receptors become unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptive properties of kinetic models that represent biochemical processes including neurotransmitter receptors have recently been analyzed from a theoretical point of view (Friedlander and Brenner, 2009). This previous work showed that first order kinetic systems similar to the type discussed here can change their gain when receptors become unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of a biological system to adjust the sensitivity in a wide range of input amplitudes, has been extensively studied in the literature10111213, especially in recent years1415161718192021222324. The phenomenon occurs in different contexts, like chemotaxis in bacteria1424 and amoeba19, osmotic regulation in yeast25, tryptophan regulation in E.coli 26, and sensory systems171213.…”
mentioning
confidence: 99%
“…The response usually includes a strong transient part, followed by adaptation which determines the steady-state at longer-times. Famous examples include cell receptors [5] and molecular signaling tasks in cells [6][7][8][9], as well as collective behaviour which is based on chemical signaling [10] such as in the case of bacteria [11]. Another important example on the cellular level is chemotaxis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%